Living with climate variation and change - A comparative study of resilience embedded in the social organization of reindeer pastoralism in Western Finnmark and Yamal Peninsula - Turi, Ellen Inga (Universitetet i Oslo, 2008)
This thesis aims to determine the role of the social organization of reindeer pastoralism in securing resilience for the livelihood, and further to determine hoe the institutional settings affect this role, focusing in particular on institutional constraints and opportunities affecting nomadic movement.